2013
DOI: 10.1111/bph.12435
|View full text |Cite
|
Sign up to set email alerts
|

Platelet P2Y12 receptors are involved in the haemostatic effect of notoginsenoside Ft1, a saponin isolated from Panax notoginseng

Abstract: BACKGROUND AND PURPOSESaponins isolated from Panax notoginseng (Burk.) F.H. Chen have been shown to relieve thrombogenesis and facilitate haemostasis. However, it is not known which saponin accounts for this haemostatic effect. Hence, in the present study we aimed to identify which saponins contribute to its haemostatic activity and to elucidate the possible underlying mechanisms. EXPERIMENTAL APPROACHPlatelet aggregation was analysed using a platelet aggregometer. Prothrombin time, activated partial thrombopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
50
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 32 publications
0
50
0
Order By: Relevance
“…Gao et al [9] showed that different NTS may either increase or decrease platelet aggregation in the same experimental setting [9], further supporting the apparently contradicting results obtained by others. The source of the herbs aside, however, discrepancy in findings may also arise from different preparation methods (e.g.…”
mentioning
confidence: 83%
See 4 more Smart Citations
“…Gao et al [9] showed that different NTS may either increase or decrease platelet aggregation in the same experimental setting [9], further supporting the apparently contradicting results obtained by others. The source of the herbs aside, however, discrepancy in findings may also arise from different preparation methods (e.g.…”
mentioning
confidence: 83%
“…Parameters of coagulation, such as prothrombin time, activated partial thromboplastin time and thrombin time, were also lengthened after Ft1 treatment [9]. This study [9] did not examine the haemostatic effect of raw notoginseng (water or alcohol extract) or dencichine, which will be of value to compare the efficacy of the various samples in the same experimental setting. Nevertheless, the enhanced platelet activity of NTS (notably Ft1) has been demonstrated.…”
mentioning
confidence: 96%
See 3 more Smart Citations